PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE LEARNING CELL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI IKATAN KIMIA DI KELAS X MIPA SMAN 5 PEKANBARU - Rahman, Abdul; ', Herdini; Linda, Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about the learning cell type of cooperative learning model has been conducted in SMAN 5 Pekanbaru. The purpose of this research is to improve the student achievement on the topic chemical bond in class X MIPA SMAN 5 Pekanbaru. The type of this research is experimental research with experiment design randomized control group pretest-posttest. Sample of the research consisted of two classes, a class X MIPA4 as an experimental class (implemented the learning cell type of cooperative learning model) and class X MIPA3 as the control class (without the learning cell type of cooperative learning model). T-test was used as analysis technique. Based on the data analysis obtained t > t table (1.80 > 1.67), meaning that the application of the learning cell type of cooperative learning model can improve the student achievement on the subject chemical bond in class X MIPA SMAN 5 Pekanbaru. The improvement of the student achievement category (N-Gain) as high as 0.73.Keywords: Student Achievement, The Learning Cell Type, Cooperative Learning, Chemical Bond.